2012
DOI: 10.1007/s12687-012-0090-4
|View full text |Cite
|
Sign up to set email alerts
|

Who is being referred to cancer genetic counseling? Characteristics of counselees and their referral

Abstract: Both physician and patient play a role in the referral process for cancer genetic counseling. Access to such counseling is not optimal because some eligible patients are not being reached by current referral practice. We aimed to identify factors associated with the initiator of referral. During a 7-month period, we recorded demographic characteristics like gender, personal and family history of cancer, ethnicity and eligibility for genetic testing for 406 consecutive counselees using a specially designed ques… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
40
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 27 publications
(42 citation statements)
references
References 45 publications
2
40
0
Order By: Relevance
“…Patients’ request for cancer genetic counseling and their concerns about family members are important determinants for cancer genetic counseling. Van Riel et al ( 2012 ) showed that the majority of counselees initiate a referral themselves (van Riel et al 2012 ), while Brandt et al ( 2008 ) found that 73% of a group of primary care physicians and specialists base patient eligibility for referral on patient request, and 54% did not refer eligible patients due to patient disinterest. When physicians are not sure whether screening is recommended, patients who expect screening and those who are more anxious, are more often referred (Haggerty et al 2005 ).…”
Section: Introductionmentioning
confidence: 99%
“…Patients’ request for cancer genetic counseling and their concerns about family members are important determinants for cancer genetic counseling. Van Riel et al ( 2012 ) showed that the majority of counselees initiate a referral themselves (van Riel et al 2012 ), while Brandt et al ( 2008 ) found that 73% of a group of primary care physicians and specialists base patient eligibility for referral on patient request, and 54% did not refer eligible patients due to patient disinterest. When physicians are not sure whether screening is recommended, patients who expect screening and those who are more anxious, are more often referred (Haggerty et al 2005 ).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, we have no data on the ethnicity of our sample. Van Riel et al (2012) showed that counselees referred for cancer GT to our department were primarily Caucasian, which should be taken into account when interpreting our results. Finally, in contrast to, for example, the U.S.A., the Netherlands is a small country.…”
Section: Study Strengths and Limitations And Research Recommendationsmentioning
confidence: 86%
“…We conducted a group interview with breast surgeons and specialized nurses, who are the main referrers to genetic counseling for patients with breast cancer [8,27] to assess their preferences regarding content and design of a training program and to gain insight into conditions to participate. They were recruited from different breast cancer teams from different hospitals in Western Netherlands.…”
Section: Assess Needs and Preferences Of Healthcare Professionals Andmentioning
confidence: 99%